Manager’s social influence on aggression management and organisational commitment / Continue Anddison Eketu … [et al.] - Eketu, Continue Anddison; Edeh, Friday Ogbu; Nawaz, Abid Hussain; Ugboego, Chukwu Agnes (UiTM Press, 2021)
The purpose of this study is to investigate manager’s social influence on the relationship between aggression management and organisational commitment using cross-sectional survey. Accessible population of five manufacturing companies operating in Enugu state was surveyed. -96 participants completed the instrument but only -182 were returned and found valid for analysis. Face validity was used to determine the validity of instrument used. Cronbach α was used to determine the reliability of the instrument. Frequency distribution and Pearson Product Moment Correlation Coefficient were used to conduct the analysis. The results of the study revealed that aggression management has positive significant relationship with organisational commitment. On the other hand, manager’s social influence positively and significantly moderates the relationship between aggression management and organisational commitment. The study concludes that aggression management measured in terms of self-control and punishment enhances organisational commitment. The implication of this study is that managers, policy makers and human resource professionals should use their social influence in handling aggressive behaviour in the workplace so as to increase the commitment of their subordinates which will in turn increase profitability, growth and expansion of the organisation.